2013
DOI: 10.1002/jcb.24586
|View full text |Cite
|
Sign up to set email alerts
|

HOX antisense lincRNA HOXA-AS2 is an apoptosis repressor in allTransretinoic acid treated NB4 promyelocytic leukemia cells

Abstract: HOXA cluster antisense RNA 2 (HOXA-AS2) is a long non-coding RNA located between the HOXA3 and HOXA4 genes in the HOXA cluster. Its transcript is expressed in NB4 promyelocytic leukemia cells and human peripheral blood neutrophils, and expression is increased in NB4 cells treated with all trans retinoic acid (ATRA). Knockdown of HOXA-AS2 expression by transduced shRNA decreases the number of viable cells and increases the proportion of apoptotic cells, measured by annexin V binding and by activity and cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 41 publications
1
79
0
Order By: Relevance
“…LncRNA could regulate the gene expression at the transcriptional or posttranscriptional level by acting as microRNA (miRNA) sponges [7]. Abnormal lncRNA expressions have been reported to be upregulated in various cancers, including PTC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA could regulate the gene expression at the transcriptional or posttranscriptional level by acting as microRNA (miRNA) sponges [7]. Abnormal lncRNA expressions have been reported to be upregulated in various cancers, including PTC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence has implicated the involvement of long non-coding RNAs (lncRNAs) in several of the steps leading to glioma development [10, 11]. The lncRNA HOXA cluster antisense RNA 2 (HOXA-AS2) was first reported to be an apoptosis suppressor in NB4 promyelocytic leukemia cells treated with all-trans retinoic acid [12]. Subsequent studies showed that HOXA-AS2 is aberrantly expressed in several human cancers and functions as an oncogene [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Consisted with previous findings, HOXA-AS2 was upregulated in some kinds of tumor cells, including acute promyelocytic leukemia and gastric cancer [19,20]. But little is known about the role of HOXA-AS2 in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA HOTAIR functions as an oncogene and high expression level of HOTAIR is correlated with metastases and survival in many cancers [14][15][16][17][18]. HOXA-AS2, a long non-coding RNA located between the HOXA3 and HOXA4 genes in the HOXA cluster, has been characterized as an oncogene in acute promyelocytic leukemia and gastric cancer, and knockdown of HOXA-AS2 inhibited cell proliferation and induced cell apoptosis [19,20]. However, whether HOXA-AS2 is involved in the progression of HCC is ill-defined and the molecular mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%